Preparation, regioselective chemistry, and electronic properties of perfluoroalkylfullerenes - Whitaker, James B., author; Strauss, Steven H., advisor; Chen, Eugene, committee member; Finke, Rick, committee member; Williams, Bob, committee member; Ridley, John, committee member (Colorado State University. Libraries, 2013)
A systematic study of how various reaction parameters affect the product distribution of gas-solid reactions was carried out in a new reactor of local design. These reactions involve the trifluoromethylation of C60, C70, and the endohedral metallofullerenes Sc3N@C80 and Y3N@C80; and in particular, the reactions were optimized to favor C60(CF3)2 and C60(CF3)4. A new solution phase homogeneous perfluoroalkylation method was used to prepare a series of 1,7-C60(RF)2 compounds with different RF chain lengths and branching patterns. A range of analytical methods including 19F NMR and UV-vis spectroscopy, APCI mass spectrometry, and X-ray crystallography were used to structurally characterize the compounds. Cyclic voltammetry, DFT E(LUMO) calculations, and gas phase electron affinity (EA) measurements were used to determine the substituent effect of the RF groups. The results conclusively showed that the solution phase E1/2, calculated E(LUMO), and EA values-- that are typically assumed to be correlated for a series of electron acceptors-- are not always correlated. Several highly efficient and selective methods were developed for the further functionalization of selected trifluoromethyl fullerenes (TMFs). These new functionalized TMFs were structurally characterized using the aforementioned analytical techniques and the X-ray crystal structures of five new derivatized TMFs were determined. Analysis of the how these newly derivatized TMFs pack in a crystalline solid revealed fullerene density values that were in general twice that of reported fullerenes that pack in the same motifs. These derivatized TMFs also exhibited extended networks of short C···C distances between fullerene cages of adjacent molecules that has been correlated to increased free charge carrier motilities in organic photovoltaic device active layers. The solution phase E1/2 values of the most commonly used fullerene derivatives in OPV devices were measured under carefully controlled conditions and revealed that poor reporting of electrochemical conditions, mistakes interpreting electrochemical data, and fullerene impurities have combined to cause significant confusion about the reported electrochemical values in the literature. A preliminary study of 32 OPV devices fabricated with active layers containing perfluoroalkylfullerenes (PFAFs) indicated that (i) PFAFs can function as suitable electron acceptors in OPVs, and (ii) that a more detailed study examining the complex electronic interplay between the fullerene electron acceptor and polymer donor is warranted.
Keywords: fullerenes; regioselective chemistry